An interaction study of online learning satisfaction with parent-child relationships and trait coping styles - Wen, Leji; Xu, Weizhuo; Yan, Xiaoyue; Lin, Xin; Shao, Chen; Zhang, Lei (Frontiers in Psychiatry, 2024)
As the physical and mental development of the young is not only influenced by the parent-child relationship (PR) and the student's academic performance, but also moderated by trait coping styles (TCS), the changes between these three during the online learning period in an epidemic need to be reconsidered. This study aims to explore the factors affecting online learning satisfaction (OLS) among students and their interaction with parent-child relationship and trait coping style. A web-based questionnaire was employed, encompassing general information, the Trait Coping Style Questionnaire (TCSQ), and queries related to OLS. A total of 1,287 valid questionnaires were collected, with 593 from junior high school students, 197 from high school students, and 497 from university students. Our findings indicate that parent-child relationship (PR), positive coping style (PCS), and learning status (LS) showed a positive correlation with OLS (r=0.110, P<0.001; r=0.786, P<0.001). Conversely, negative coping style (NCS) presented a negative correlation with OLS (r=-0.186, P<0.01). Multiple regression analysis of OLS reveals that PR has a significant impact on OLS (P<0.001, β=0.291), as does LS (P<0.001, β=0.767). However, trait coping styles (TCS) appear to have no significant effect on OLS. Notably, PR plays a significant and positive mediating role between LS and OLS, with a mediation effect of 0.0132 (P<0.05), accounting for 1.682% of the total effect. These findings suggest that strengthening parent-child interactions and fostering adaptive coping mechanisms could play a crucial role in enhancing students' satisfaction with online education. Such improvements could potentially contribute to superior academic outcomes and overall student well-being.